PELATIHAN PEMBUATAN VIRGIN COCONUT OIL (VCO) PADA DESA OMA, PULAU HARUKU, MALUKU TENGAH - Mirella Fonda Maahury; Catherina M. Bijang; A. Netty Siahaya; Nurani Hasanela; Mario Rowan Sohilait (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Mataram, 2021)
Virgin coconut oil (VCO) is one of the processed products from coconuts that has high economic value. This economic value is triggered by the benefits of VCO. The people of Oma Village are located on the coast of Haruku Island which is very overgrown with coconut plants. The abundance of coconut plants has not been maximally utilized by the Oma village community. This problem prompted training to make VCO for the Oma village community, Haruku Island. This community service is carried out based on counseling and training on making VCO to the Oma Village community. Counseling was carried out to convey about VCO, the benefits of VCO and how to make VCO. The training is carried out by demonstrating/demonstrating the procedure for making VCO and providing tools and materials to partners to be able to produce VCO independently. The results of VCO products from the Oma Village community are reported to the service team and used as an indicator of the success of the VCO making training. The results obtained provide information that this product is a product that can be cultivated by the Oma village community as an opportunity to improve their economy.